Leaf Litter Production and Decomposition in Dalbergia sissoo and Bombax ceiba Plantations in Uttar Pradesh - Singh, Omkar; Sharma, D. C.; Negi, M. C.; Singh, Rajinder (Indian Forester, 1994)
Annual leaf litter fall was estimated in plantations of Dalbergia sissoo and Bombru ceiba as 1893 and 1303 kg/ha. The corresponding decomposition parameters were estimated as 1.32 and 1.67 respectively. Time required for various levels of decay has been worked out and mineralsation of nutrients has also heen discussed.